Monitoring archaeological site landscapes in Cyprus using multi-temporal atmospheric corrected image data - Agapiou, Athos; Themistocleous, Kyriacos; Clayton, Chris R I; Hadjimitsis, Diofantos G. (My University, 2009)
This paper aims to examine the use of satellite remote sensing for monitoring archaeological and more generally cultural heritage sites. For this purpose, multi-temporal data from Landsat 5 TM, Landsat 7 ETM+ and Quickbird images were applied. The paper also discusses the importance of atmospheric correction at the pre-processing step in order to determine true surface reflectance values by removing these effects from satellite images. Atmospheric correction is arguably the most important part of the pre-processing of satellite remotely sensed data and any omission produces erroneous results. The effects of the atmosphere are more severe where dark targets are shown in the satellite image. In the management of cultural heritage sites, since temporal satellite images are required for monitoring purposes, the effect of the atmosphere must be considered. In-situ spectro-radiometric measurements using the GER1500 field spectro-radiometer have been used to assess the reflectance values found after applying the darkest pixel atmospheric correction to the image data. The study area consist the Amathus archaeological site in Limassol and the Nea Paphos archaeological site area located in Paphos district area in Cyprus. Vegetation Index (NDVI) change detection algorithm has been applied to a series of thirteen Landsat TM/ETM+ images of Amathus archaeological site in Limassol. Classification and extraction algorithms have been applied to Landsat TM and Quickbird high resolution images of Nea Paphos archaeological site area
Keywords: Architecture; Architectural design; Environmental archaeology; Atmosphere